Leveraging tele-mentoring and remote learning to strengthen the emergency care capacity of health workers in Uganda - Atuhairwe, Irene; Ngabirano, Annet Alenyo; Ahaisibwe, Bonaventure; Nsubuga, Allan; Kanyike, Andrew Marvin; Kihumuro, Raymond Bernard; Balizzakiwa, Thomas; Ewing, Helen; Ellis, Randall; Forbush, Leigh; Joseph, Oumo; Nakyeyune, Marion Jane; et al. (African Journal of Emergency Medicine, 2023)
Background: A robust emergency care system is a cost-effective method of reducing preventable death and dis- ability, especially in low-and middle-income countries. To scale emergency care expertise across the country, the Uganda Ministry of Health and Seed Global Health established the Emergency Medical Services (EMS) ECHO program. We describe the process of establishing the program in a resource-limited setting, best practices, and lessons learned in Uganda. Methods: Investigators conducted a mixed-methods evaluation to assess the initial 4 months’ implementation of the EMS ECHO. We conducted pre/post-program assessments of healthcare worker knowledge, self-efficacy, and professional’s satisfaction with the program. The analysis compared the differences between pre/post-test scores descriptively. Results: The EMS ECHO was initiated in November 2021. A phased curriculum was developed with the initial phase focusing on the ABCDE (Airway, Breathing, Circulation, Disability, and Exposure) approach to the emergency patient. This phase reached 2,030 health workers cumulatively across 200 health facilities. The majority of the participants were medical doctors ( n = 751, 37%), and nurses ( n = 568, 28%). Majority of participants (95%) rated the sessions as informative. On whether the ECHO sessions diminished professional isolation, 66% agreed or strongly agreed. Conclusions: Similar to other ECHO program evaluation results, Uganda’s EMS ECHO program improved knowledge, skills, and the development of a virtual community of practice thereby diminishing professional isolation. It also demonstrates that through a planned stepwise process, virtual learning and tele-mentorship can be used efficiently to improve healthcare worker knowledge, skills and multiply the limited number of emergency care experts available in the country.
Keywords: Emergency medicine; ECHO; Telemedicine